The Battle of Ideology: Seeking the Strategy for Indoctrinating Pancasila for Those Who Are Anti-Pancasila - Munajat, Munajat (Millati: Journal of Islamic Studies and Humanities, 2022)
The present article aims to explore the strategy of indoctrinating Indonesian state ideology, Pancasila, towards the anti-Pancasila groups. The data is primarily based on the combination of primary data from the interview with the guardians of terrorists from eight prisons in Indonesia and secondary data from the open-source internet data. The study finds that the strategy for indoctrinating the Pancasila ideology must consider classifying people’s level of disagreement with the Pancasila ideology, namely: supporter, follower, and militant. Supporters are those who are anti-Pancasila without having any plausible reasons. Therefore, the key to the problem lies in the socialization of Pancasila, which includes the educational and cultural approaches. Followers are anti-Pancasila and have reasons not to like Pancasila but do not show it to the public. Therefore, the key to solving the problem is not only the socialization of Pancasila but also the deconstruction of their understanding of Pancasila. The anti-Pancasila militants have reasons not to like Pancasila and actively promote and oppose Pancasila. The key to responding to it is combining hard and soft approaches in indoctrinating Pancasila.